The Exploitation Reserve Army of Labour in The Rural Capitalism: Oil Palm Plantation StudyIn Bualemo District, Banggai Regency, Central Sulawesi Province - Ichwal Moidady, Nuzulul; Soetarto, Endriatmo; Agusta, Ivanovich (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTThe objective of this study is to describe and examine how reserve army of labour exploitation and mobilization conducted by plantation (oil palm) torural labour. This research was took mobilization laobur analyzis such asrecruitment and disciplined. Subsequently, exploitation theory have to analyzesthrough labour time, wages, and means of production use. The results showe that casual labour day(Buruh Harian Lepas) recruit by foreman(mandor) and plantation assistant. Moreover, they are then disciplined in a certain way, i.e settledfrom their homes to the plantation afdeling camp. On the other hand, the exploitation is done through the application of long working time (surplus labour time)and low wage when doing nursery and cultivation. Beside that, they used simple production tools (non mechanization) such, dodos (harvester), axe, and means of transporters (truck and dump)to carry out fresh fruit bunch (Tandan Buah Segar). They used input of production such, sprayer (mechanization), fertilizer (NPK) and herbicide (chemical) with the intensive working day.Keyword: exploitation, reserve army of labour, means of productionABSTRAKPenelitian ini bertujuan menguraikan dan membuktikan bagaimanapengerahan dan eksploitasi tenaga kerja cadangan dilakukan oleh perkebunan skala besar (kelapa sawit) terhadap rakyat pekerja di pedesaan.Penelitian ini mengunakan analisispengerahan tenaga kerja yang meliputi: rekrutmen dan pendisiplinan tenaga kerja. Kemudian, teori eksploitasi dianalisis melalui: waktu kerja, pengupahan, dan pengunaan alat-alat produksi.Hasil penelitian menunjukan buruh harian lepas (pekerja tidak tetap) direkrut oleh mandor dan asisten kebun.Mereka kemudian didisiplinkan melalui cara tertentu, yaitu dimukimkan di camp kerja afdeling perkebunan. Pada sisi yang lain, tindakan eksploitasi dilakukan melaui penerapan waktu kerja yang panjang dan upah harian yang rendah pada saat mengerjakan pembibitan dan penanaman.Selain itu,buruh harian lepas juga menggunaan alat-alat produksi sederhana(non mekanisasi)seperti dodos(alat panen), kampak, dan alat pengangkut (truck dan bak penampung)untuk mengerjakan panen tandan buah segar (TBS). Mereka juga menggunakan input produksi sprayer (mekanisasi), pupuk NPK dan herbisida (kimia) dengan waktu kerja yang intensif.Kata Kunci: eksploitasi, tenaga kerja cadangan, alat-alat produksi